“M-Commerce- Facilitator Of E-Commerce” - ., Chitrangda (International Journal of Scientific Research and Management (IJSRM), 2014)
Mobile phones are central to the lives of most people in developed countries and are growing in importancein less developed countries. Since their mainstream adoption in the 1990s, they have remained primarilycommunication devices. We use mobile phones to talk to other people and we carry mobile phones with usso that other people can talk to us. However, the situation is changing. Mobile phone manufacturers have developed mobile devices that canserve many functions beyond voice communication such as taking photos and listening to music. Mobilenetwork operators are offering services that give greater value to subscribers, such as portable email forbusiness users. Mobile phones are now equipped with cameras with the potential to turn them into portablebar code scanners. Handset manufacturers are developing Radio-frequency Identification (RFID) chips thatcan turn mobile phones into mobile wallets able to carry and exchange electronic money securely andengage in other transactions with RFID readers in the physical world. The combination of more powerful mobile devices, more innovative mobile operators and change in themobile network infrastructure (such as 3G networks able to carry large amounts of data at high speed asbroadband connections do for computers) is setting the stage for an enormous change in a already fast-moving sector. Mobile devices are fast becoming the place where numerous technologies meet and createapplications that are useful for both consumers and businesses across the globe. All these activities fallunder M-commerce. The mobile phone of the future is a device that enables users to communicate, connect, transact andinnovate